2011
DOI: 10.1016/j.jmb.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Conformation Effects of Base Modification on the Anticodon Stem–Loop of Bacillus subtilis tRNATyr

Abstract: tRNA molecules contain 93 chemically unique nucleotide base modifications that expand the chemical and biophysical diversity of RNA and contribute to the overall fitness of the cell. Nucleotide modifications of tRNA confer fidelity and efficiency to translation and are important in tRNA-dependent RNA-mediated regulatory processes. The three-dimensional structure of the anticodon is crucial to tRNA-mRNA specificity and the diverse modifications of nucleotide bases in the anticodon region modulate this specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 65 publications
4
40
0
Order By: Relevance
“…Preliminary studies to identify and optimize conditions that stabilize the SD-ASL Gly complex demonstrated that Mg 2+ was necessary. Addition of Mg 2+ to ASL Gly disrupts the C 32 -A + 38 base pair of the hairpin [17, 18] , but has little effect on the NH spectrum (Figure 2B). Addition of Mg 2+ to SD reinforces the loop E motif as evidenced by the appearance of NH resonances for nucleotides U 12 and G 26 that participate in reverse Hoogsteen U-A and sheared A-G base pairs, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies to identify and optimize conditions that stabilize the SD-ASL Gly complex demonstrated that Mg 2+ was necessary. Addition of Mg 2+ to ASL Gly disrupts the C 32 -A + 38 base pair of the hairpin [17, 18] , but has little effect on the NH spectrum (Figure 2B). Addition of Mg 2+ to SD reinforces the loop E motif as evidenced by the appearance of NH resonances for nucleotides U 12 and G 26 that participate in reverse Hoogsteen U-A and sheared A-G base pairs, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…10,33,46 NMR spectra were collected on a DMX Bruker 500-MHz instrument equipped with a tripleresonance 1 H, 13 C, and 15 N probe and three-axis pulsed field-gradient capabilities and on a Varian INOVA 600-MHz instrument equipped with a cryoprobe. All NMR data were processed using NMRPipe.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The majority of modifications and the most chemically complex occur at position 34 or at position 37, immediately 3′ adjacent to the anticodon triplet. These anticodon domain modifications alter conformation and thermal stability, 4-10 enhance decoding specificity, [10][11][12][13][14] enhance ribosomal binding, 4,6,[15][16][17] promote proper translocation 17 and maintain the translational reading frame. [18][19][20][21] Anticodon domain modifications have been shown to be essential for prestructuring the ASL toward a canonical U-turn structure in solution for proper recognition in the ribosomal A-site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, Ψ's can stabilize tRNA folding and increase the fidelity of codon-anticodon interactions, stabilize certain stem-loop conformations of snRNAs, and enable ribosome assembly (Yarian et al 1999;Greenbaum 2001, 2002b;Nobles et al 2002;Cabello-Villegas and Nikonowicz 2005;Denmon et al 2011;Jack et al 2011;Penzo et al 2015). The majority of indications that pseudouridylation plays an important biological role stems indirectly from the observation that Ψ's are modulated in response to different cellular conditions.…”
Section: Introductionmentioning
confidence: 99%